Evaluasi Penggunaan Analgesik pada Pasien Sectio caesarea di Rumah Sakit St. Elisabeth Semarang - Paulina Maya Octasari (Jurnal Farmasi Indonesia, 2022)
Section caesarea (SC) is a one birth methods by surgery if the mother has a difficult way to take the baby out by vagina. At 2010 year, Indonesia have prevalence of section caesarea as 15.3% from 20.591 mother over five last year in 33 province. One of the most mother birth have symptoms, is pain. Ketorolac is the one of analgesic as a first choice for cesarean section patients. This research aims to evaluate the analgesic usage in cesarean section patients at St. Elisabeth Hospital, Semarang. This research is an observasional descriptive research with retrospektive data. Data was collected from sc patient who was given ketorolac after SC on July – December 2017 at St. Elisabeth Hospital, Semarang. The inclusion criteria were patient with JKN assurance and patients who had SC for the first time. The data were analyzed qualitatively and quantitavely The result shows that the most patients were 26 – 30 years old. The amount of the patients after was given ketorolac who had mild pain scale were 95.1% and moderate pain scale were 4.9%. The average pain scale was slightly decrease over 3 – 4 hours after injection, as 1,46 scale. The most kind of analgesic who used as an extra were tramadol (32.93%). Mefenamic acid and diclofenac natrium was the biggest amount to use at home.